Evaluation of a Multiplex PCR Panel for the Microbiological Diagnosis of Pneumonia in Hospitalized Patients: Experience from an Academic Medical Center. (March 2021) - Zacharioudakis, Ioannis M.; Zervou, Fainareti N.; Dubrovskaya, Yanina; Inglima, Kenneth; See, Benjamin; Aguero-Rosenfeld, Maria
Highlights: Diagnostic tests performed for the microbiological diagnosis of pneumonia as per standard of care were able to identify an agent in 56% of cases. Addition of a multiplex PCR panel increased the microbiologic yield to 84.3%, implying that 17/20 of patients will receive a microbiological diagnosis of pneumonia within hours or testing. We found potential for antimicrobial optimization in 80% of patients diagnosed with pneumonia, including 13% of patients who were not covered by the empirical antimicrobial regimen. Abstract: Objectives: We evaluated the value of BioFire® FilmArray® pneumonia panel in establishing a microbiological diagnosis of pneumonia. We evaluated opportunities for antimicrobial optimization from its use. Methods: We included adult patients with pneumonia between May 2019 and January 2020. The pneumonia panel was used on high-quality sputum specimens, and the results were prospectively compared with sputum cultures and other tests performed according to standard of care. Results: Seventy patients were included, sixty-nine of whom completed a 5-day antimicrobial course for pneumonia, and 14.3% died during hospitalization. There was a trend of higher rate of microbiological diagnosis among the patients with culture submitted before antimicrobial administration (9/15 vs. 20/55; p = 0.09). The panel increased the microbiological diagnosis from 29/70 to 59/70 (p < 0.001) patients. The per isolate analysis revealed an increase in the isolation of Haemophilus influenzae (p = 0.002) and Streptococcus pneumoniae (p = 0.05). On review of empiric antimicrobials, there was potential for antimicrobial optimization in 56/70 patients, including 9 bacteria among 9 patients, which were not covered by empiric treatment and another 70 antimicrobials in 49 patients that could have been stopped. Conclusions: Incorporation of the pneumonia panel in the diagnostic work-up of pneumonia substantially increased the rate of microbiological diagnosis and revealed abundant opportunities for antimicrobial optimization.